The Status of Three Northern Migrant Raptors Rarely Observed on Java - Vincent Nijman (KUKILA, 2003)
In the course of a study on raptor migration the central Java, Indonesia, during the periods September-January 1998 and September-October 1999, three species were recorded which have rarely, if ever, been recorded on the island: Common Buzzard Buteo buteo, Booted Eagle Hieraaetus pennattts and Marsh Harrier Circus aeruginosus. Based on a study of the literature and museum skins, and previous experience with the respective species, their identification and status in the Indo-Malayan region is discussed. Raptors migrating through Java originate from northern Asia and might migrate further to Bali and possibly the Lesser Sunda Islands. All species are essentially open woodland species. The increase in the number of migrant species observed on Java and Bali is most likely due to an increase in focused research accompanied by better identification techniques but may also indicate an expansion of species' ranges due to changing land-use in western Indonesia, with closed canopy forest being increasingly replaced by more open types of forest and cultivated land.